Harm reduction for the treatment of patients with severe injection-related infections: description of the Jackson SIRI Team - David P. Serota; Hansel E. Tookes; Belén Hervera; Babley M. Gayle; Cara R. Roeck; Edward Suarez; David W. Forrest; Michael A. Kolber; Tyler S. Bartholomew; Allan E. Rodriguez; Susanne Doblecki-Lewis (Annals of Medicine)
Introduction Hospitalizations for severe injection-related infections (SIRI), such as endocarditis, osteomyelitis, and skin and soft tissue infections (SSTI) are increasingly common. People who inject drugs (PWID) experiencing SIRIs often receive inadequate substance use disorder (SUD) treatment and lack of access to harm reduction services. This translates into lengthy hospitalizations with high rates of patient-directed discharge, readmissions, and post-hospitalization mortality. The purpose of this study was to describe the development of an integrated “SIRI Team” and its initial barriers and facilitators to success.Materials and methods The Jackson SIRI Team was developed to improve both hospital and patient-level outcomes for individuals hospitalized with SIRIs at Jackson Memorial Hospital, a 1550-bed public hospital in Miami, Florida, United States. The SIRI Team provides integrated infectious disease and SUD treatment across the healthcare system starting from the inpatient setting and continuing for 90-days post-hospital discharge. The team uses a harm reduction approach, provides care coordination, focuses on access to medications for opioid use disorder (MOUD), and utilizes a variety of infection and addiction treatment modalities to suit each individual patient.Results Over the initial 8-months of the SIRI Team, 21 patients were treated with 20 surviving until discharge. Infections included osteomyelitis, endocarditis, bacteraemia/fungemia, SSTIs, and septic arthritis. All patients had OUD and 95% used stimulants. All patients were discharged on MOUD and 95% completed their prescribed antibiotic course. At 90-days post-discharge, 25% had been readmitted and 70% reported taking MOUD.Conclusions A model of integrated infectious disease and SUD care for the treatment of SIRIs has the potential to improve infection and addiction outcomes. Providing attentive, patient-centered care, using a harm reduction approach can facilitate engagement of this marginalized population with the healthcare system.KEY MESSAGESIntegrated infectious disease and addiction treatment is a novel approach to treating severe injection-related infections.Harm reduction should be applied to treating patients with severe injection-related infections with a goal of facilitating antibiotic completion, remission from substance use disorder, and reducing hospital readmissions.